2013
DOI: 10.1186/1477-7525-11-183
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity, sedentary behavior and total wellness changes among sedentary adults: a 4-week randomized controlled trial

Abstract: BackgroundThe construct of total wellness includes a holistic approach to the body, mind and spirit components of life. While the health benefits of reducing sedentary behavior and increasing physical activity are well documented, little is known about the influence on total wellness of an internet-based physical activity monitor designed to help people to achieve higher physical activity levels.PurposeThe purpose of this four-week, personal activity monitor-based intervention program was to reduce sedentary b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
112
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(115 citation statements)
references
References 29 publications
3
112
0
Order By: Relevance
“…Three studies employed an intervention specifically to reduce SB,40 44 63 16 studies aimed at increasing PA levels,30 35 36 39 41 46 48 49 55 58–60 64 66 72 78 nine studies combined both approaches of reducing SB and increasing PA levels,32 43 53 62 65 68 70 76 77 one study assessed the effect of a dietary intervention on SB,61 and 22 studies (20 reports) applied a multicomponent lifestyle intervention and observed effects on sedentary behaviour (among other outcomes) 29 33 34 37 38 42 45 47 50–52 54 56 57 67 69 71 73 74 75. Twenty studies offered an alternative intervention,30 36 39–41 45 46 49 52–55 59 61–63 68 72 77 10 studies the usual/routine care,29 37 38 42 50 51 67 71 74 75 seven studies used a waiting list control,29 34 48 64 69 76 78 five studies an attention control,35 44 56 57 60 and control participants of seven studies received no intervention at all 32 33 43 47 58 66 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three studies employed an intervention specifically to reduce SB,40 44 63 16 studies aimed at increasing PA levels,30 35 36 39 41 46 48 49 55 58–60 64 66 72 78 nine studies combined both approaches of reducing SB and increasing PA levels,32 43 53 62 65 68 70 76 77 one study assessed the effect of a dietary intervention on SB,61 and 22 studies (20 reports) applied a multicomponent lifestyle intervention and observed effects on sedentary behaviour (among other outcomes) 29 33 34 37 38 42 45 47 50–52 54 56 57 67 69 71 73 74 75. Twenty studies offered an alternative intervention,30 36 39–41 45 46 49 52–55 59 61–63 68 72 77 10 studies the usual/routine care,29 37 38 42 50 51 67 71 74 75 seven studies used a waiting list control,29 34 48 64 69 76 78 five studies an attention control,35 44 56 57 60 and control participants of seven studies received no intervention at all 32 33 43 47 58 66 …”
Section: Resultsmentioning
confidence: 99%
“…Twenty studies indicated a beneficial effect of interventions for reducing SB in favour of the intervention group. Of these, 10 studies employed a lifestyle intervention,29 33 34 37 38 42 51 52 54 74 six studies targeted increase in PA,30 41 46 48 64 78 two studies were combined PA/SB interventions32 68 and two studies were SB interventions 40 63. Two studies reported a beneficial intervention effect in favour of the control group;39 60 both studies were PA interventions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These wearable devices are worn on different body parts in these studies as per monitor instructions. Studies using Fitbit [39], MTx-W [50] Gruve [42] and PAM [46] required the devices to be worn along the iliac crest. Fitzsimons et al"s [44] study, which used activePAL as a monitoring device required it to be worn along the upper thigh.…”
Section: Systematic Review Of Fitness Wearable Devicesmentioning
confidence: 99%
“…We used keywords mentioned in the table below ( The systematic review methodology has been adopted from Lewis et al [5] and the flow chart below shows the methodology of the systematic review. In the twelve studies selected, each one was based on a different wearable device: Fitbit [30][31][32][33][34][35][36][37][38][39][40][41], Gruve [42] Bluetooth Actiwatch [43], activPAL [44], PAM [45][46] Sense Wear armband [47][48][49] and MTx-W sensor [50].…”
Section: Systematic Review Of Fitness Wearable Devicesmentioning
confidence: 99%